2005
DOI: 10.1111/j.1365-2958.2005.04871.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of a novel anionic polysaccharide from Porphyromonas gingivalis strain W50 related to Arg‐gingipain glycans

Abstract: SummaryThe Arg-gingipains (RgpsA and B) of Porphyromonas gingivalis are a family of extracellular cysteine proteases and are important virulence determinants of this periodontal bacterium. A monoclonal antibody, MAb1B5, which recognizes an epitope on glycosylated monomeric RgpAs also cross-reacts with a cellsurface polysaccharide of P. gingivalis W50 suggesting that the maturation pathway of the Arg-gingipains may be linked to the biosynthesis of a surface carbohydrate. We report the purification and structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
169
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(175 citation statements)
references
References 55 publications
5
169
1
Order By: Relevance
“…We reasoned that a flippase-deficient strain would be useful to determine whether P. gingivalis O antigen chains contribute to OMV formation. The porR locus is involved in A-LPS biosynthesis (15,26); however, not all of the genes in that locus have been characterized (supplemental Fig. S1).…”
Section: Mutation In Pors Flippase Affects A-lps Biosynthesis-thementioning
confidence: 99%
See 1 more Smart Citation
“…We reasoned that a flippase-deficient strain would be useful to determine whether P. gingivalis O antigen chains contribute to OMV formation. The porR locus is involved in A-LPS biosynthesis (15,26); however, not all of the genes in that locus have been characterized (supplemental Fig. S1).…”
Section: Mutation In Pors Flippase Affects A-lps Biosynthesis-thementioning
confidence: 99%
“…LPS is composed of lipid A, a core oligosaccharide, and a long polysaccharide chain named O antigen or O polysaccharide. The human oral pathogen Porphyromonas gingivalis, a major causative agent of chronic periodontitis, produces two classes of LPS, carrying either neutral (O-LPS) (13) or negatively charged (A-LPS) O antigen chains (14,15). In other bacterial species containing both neutral and negatively charged O polysaccharides, only the latter has been found in the OMV.…”
mentioning
confidence: 99%
“…Genesis of these factors may share common pathways as suggested previously, in respect to µ-oxo-bisheme, responsible for the black pigment. Since a monoclonal antibody (MAb1B5) raised against the Arg-gingipain RgpA cross-reacted with a cell-surface polysaccharide of P. gingivalis strain W50 (A-LPS) [24,63], it was suggested that the maturation pathway of the Arg-gingipains could be linked to the biosynthesis of a surface carbohydrate [24]. The cross-reacting APS, different from the LPS and serotype capsule polysaccharide, was found to be a phosphorylated branch of mannan backbone.…”
Section: Biosynthesis Of A-lps and Glycosylation Of Arg Gingipains Shmentioning
confidence: 99%
“…This lead to the proposal that the Manα1–2Manα1-phosphate fragment constitutes part of the epitope recognized by MAb1B5. This phosphorylated branched mannan represented a new polysaccharide that appears immunologically connected to the post-translational additions of Arg-gingipains [24,63]. Accordingly, there seem to be common steps in the biosynthesis of A-LPS and the glycosylation of Arg gingipains in P. gingivalis .…”
Section: Biosynthesis Of A-lps and Glycosylation Of Arg Gingipains Shmentioning
confidence: 99%
See 1 more Smart Citation